Effect of an intervention based on socio-ecological model in promoting physical activity of female employees - Amineh Sahranavard Gargari; Fatemeh Sadat Hosseini; Malek Ahmadi (Gonabad University of Medical Sciences, 2018)
Although active life style is one of the main determining factors of health, the level of regular physical activities in women is less than in men and even this level decreases with aging. The aim of this study was to determine the effect of an intervention based on the social ecological model on promotion of physical activity among female employees. In this study, 160 women employed at Shabestar universities were selected, and randomly divided into two groups of control (n=80) and intervention (n=80). The intervention group received an instructional program according to the model, including one session for general instruction and four sessions for group discussion along with daily walking for 30 minutes within 8 weeks. In order to objectively measure the physical activity, the pedometer was used and to measure the perceived physical activity, the long form of International Physical Activity Questionnaire (IPAQ) was applied. The variables related to the components of socio-ecological model were measured using the socio-ecological model questionnaire. A significant difference was found between two groups after the intervention in terms of That is, the average number of steps in walking in the intervention group increased significantly (from 4204 to 7882 steps per day), while it did not significantly increase in the control group. Thus, it can be argued that designing and implementing the interventional programs based on the socio-ecological model can promote physical activity behavior among employed women